2013
DOI: 10.1128/cvi.00622-12
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Immunogenicity of Mannheimia haemolytica Vesicles

Abstract: b Mannheimia haemolytica, a major causative agent in bovine respiratory disease, inflicts extensive losses each year on cattle producers. Commercially available vaccines are only partially efficacious. Immunity to M. haemolytica requires antibodies to secreted toxins and outer membrane proteins (OMPs) of the bacterium. Gram-negative bacteria produce membrane blebs or vesicles, the membrane components of which are primarily derived from OMPs. Accordingly, vesicles have been used as immunogens with various degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…4A and B). Our results correlate well with other examples of extracellular vesicles containing a variety of proteins, such as membrane proteins, cytoplasmic and intracellular proteins (Ayalew et al, 2013; Lee et al, 2007; Lee et al, 2009; Pierson et al, 2011). In contrast to previous study which indicated that vesicles secreted from another Gram-positive bacteria Staphylococcus aureus were especially enriched with extracellular proteins (Lee et al, 2009), our data demonstrated that only a small part of “extracellular region” (0.4%) proteins were identified in CP4 MVs (Fig.…”
Section: Resultssupporting
confidence: 88%
“…4A and B). Our results correlate well with other examples of extracellular vesicles containing a variety of proteins, such as membrane proteins, cytoplasmic and intracellular proteins (Ayalew et al, 2013; Lee et al, 2007; Lee et al, 2009; Pierson et al, 2011). In contrast to previous study which indicated that vesicles secreted from another Gram-positive bacteria Staphylococcus aureus were especially enriched with extracellular proteins (Lee et al, 2009), our data demonstrated that only a small part of “extracellular region” (0.4%) proteins were identified in CP4 MVs (Fig.…”
Section: Resultssupporting
confidence: 88%
“…It is possible that this type of mechanism may be relevant in additional Pasteurellaceae spp., considering that OMVs capable of modulating the host's immune responses are liberated by several of the species associated with inflammatory conditions in different mammalian hosts, e.g., Actinobacillus pleuropneumoniae, H. influenzae, Mannheimia haemolytica, and Pasteurella multocida (72)(73)(74)(75). Further studies assessing their full immunogenic potential in animal models may generate a more complete picture of the roles of A. actinomycetemcomitans OMVs in periodontal inflammation and attachment loss.…”
Section: Discussionmentioning
confidence: 99%
“…1 for a comprehensive review covering aspects of OMV purification). In most cases, in addition to outer-membrane components, OMV proteomes include inner-membrane and cytoplasmic proteins 52,5963 ; in fact, it is exceptional if no inner-membrane and cytoplasmic components are found 64 . Importantly, even in those cases in which the samples were rigorously prepared, purified and analysed, some inner-membrane and cytoplasmic components were still detected in OMVs 65,66 .…”
Section: Omv Protein Cargomentioning
confidence: 99%
“…Recently, studies have advanced the utility of OMVs against the human pathogens Neisseria meningitidis, Francisella tularensis subsp. novicida, Burkholderia pseudomallei and Mannheimia haemolytica 59,134136 . The native contextual presentation of bacterial surface antigens in complex with an adjuvant (lipopolysaccharide (LPS)) makes OMVs an effective means to generate an adaptive immune response.…”
Section: Figurementioning
confidence: 99%